Avaliação da gentamicina aplicada em ovos de aves reprodutoras pesadas e seu efeito residual nos tecidos - Magenis, Giovana Bongiolo [UNESP] (2015)
The concern of the poultry industry to maintain high levels of productivity and food security has spurred preventive actions in order to prevent the introduction of pathogens in the poultry system. The use of gentamicin associated with in ovo vaccination has been widely used for this purpose. In particular, there is little information available in the literature about the clinical and food safety of gentamicin when applied in ovo. Given this, two experiments were conducted to evaluate the effect of the administration of gentamicin in eggs of breeders in physical, hematological and biochemical parameters, as well as the permanence of this antimicrobial in broiler tissues. In the first study, 200 eggs of Cobb arrays were used and, in the 18th day of incubation, 100 eggs received only vaccination against Marek's disease (CG) and the other 100 received the vaccine with 0.22mg/egg of gentamicin sulfate (GT). After the birth (D0), physical examinations were performed at times D+3, D+6, D+10, D+14 and D+21 (3, 6, 10, 14 and 21 days after birth, respectively), as well as additional tests on D+6, D+10, D+14 to D+21. The physical parameters covered weighing, evaluation of body condition, behavior, posture/gait, breathing, appetite, feces, feathers and skin, as well as signs of intoxication. As for the laboratory parameters, the complete blood count and serum biochemical tests [urea, uric acid, aspartate aminotransferase, alanine aminotransferase (ALT), gamma glutamyl transferase (GGT), creatine kinase, albumin and total plasma proteins] were determined. The results were statistically analyzed using the General Linear Models Procedure (GLM) of SAS with Tukey's test, with a significance level of 5%. In both groups, all birds showed healthy throughout the study and the average body weight was not significantly different between GC and GT. In the complete blood count, despite variations within the same treatment, no significant differences between ...